COMT Val158Met–Stress Interaction in Psychosis: Role of Background Psychosis Risk - Collip, Dina (CNS Neurosci Ther, 2010)
Background: The interplay between the catechol‐O‐methyltransferase (COMT) Val158Met polymorphism and environmental stress may have etiological relevance for psychosis, but differential effects have been reported in healthy control and patient groups, suggesting that COMT Val158Met interactions with stress may be conditional on background genetic risk for psychotic disorder. Methods: Patients with a nonaffective psychotic disorder (n = 86) and control participants (n = 109) were studied with the experience sampling method (a structured diary technique) in order to assess stress, negative affect and momentary psychotic symptoms in the flow of daily life. Results: Multilevel analyses revealed significant three‐way interactions between group status (patient or control), COMT genotype and stress in the model of negative affect (χ(2)(2) = 13.26, P < 0.01) as well as in the model of momentary psychotic symptoms (χ(2)(2) = 6.92, P < 0.05). Exploration of the three‐way interaction revealed that in patients, COMT genotype moderated the association between stress and negative affect (χ(2)(4) = 11.50, P < 0.005), as well as the association between stress and momentary psychosis (χ(2)(4) = 12.79, P < 0.005). Met/Met genotype patients showed significantly increased psychotic and affective reactivity to stress in comparison to the Val/Met and Val/Val genotypes. In contrast, healthy controls did not display large or significant COMT Val158Met X stress interactions. Conclusions: Important differences exist in the effect of COMT Val158Met on stress reactivity, which may depend on background risk for psychotic disorder. Differential sensitivity to environmental stress occasioned by COMT Val158Met may be contingent on higher order interactions with genetic variation underlying psychotic disorder.